The prevalence of religiosity and association between religiosity and alcohol use, other drug use, and risky sexual behaviours among grade 8-10 learners in Western Cape, South Africa - Francis, J.M.; Myers-Franchi, Bronwyn; Nkosi, S.; Williams, P.P.; Carney, T.; Lombard, C.; Nel, E.; Morojele, N. (PUBLIC LIBRARY SCIENCE, 2019)
Background: Alcohol and other drug use (AOD) and risky sexual behaviours remain high among adolescents in South Africa and globally. Religiosity influences, mitigates and provides resilience against engaging in risky behaviours among young people but few South African studies have explored potential associations between religiosity, AOD use and risky sex. We report the prevalence of religiosity and association between religiosity and AOD use and risky sexual behaviours among learners in the Western Cape Province, South Africa.